Best practices on user driven services: experience of Dar Al-Hikmah library’s maintenance of legal resources - Abu Bakar, Irni Izwah; Abu Bakar, Yusrina (Department of Library and Information Science, Faculty of Computer Science and Information Technology, University of Malaya & University of Malaya Library, 2019)
A law library exists not only to store legal collections or resources but is also there to provide services to its users with specific information needs in legal study, research and practice. This is especially so in the world where changes in information technology, communication, teaching and learning styles are even more rampant. The services designed and offered must be driven to fulfill this specific needs of its users. The staff in charge of a law library also must possess knowledge about legal resources and the skill to retrieve them in order to serve their customers better. For this reason, this article illustrated the best practices on the maintenance and provision of service of the International Islamic University Malaysia Library’s legal collection. This is a reflective paper based on review of related literature; the authors’ observation and experience in managing the legal collection in the Dar al-Hikmah Library and the authors’ effort in designing services which suit the specific needs of its users. The customers served are the internal customers within the university and external customers which includes the general public or private companies who have specific interest in legal resources. The paper also explained that to keep abreast with the changes in the needs of the customers, the Library also designed a continuing educational plan for its staff. Topics discussed include organizing the Library’s legal resources; arrangement of the study areas; marketing the Library’s legal resources and outreaching customers; and strengthening the law Library staff’s hybrid skills and knowledge on legal resources, both in printed and online formats. The paper exemplified that an excellent mesh between good collection management, provision of service which meet the specific needs of its users and continuing education of the staff is the best approach in handling a law library. These best practices could be an exemplary model to any other law libraries.